Integrated analysis of gut microbiome and its metabolites in ACE2-knockout and ACE2-overexpressed mice - Song, Lini; Ji, Wenyi; Cao, Xi (Frontiers in Cellular and Infection Microbiology, 2024)
Background Aberrant activation of the classic renin–angiotensin system (RAS) and intestinal micro dysbiosis adversely affect insulin resistance (IR), dyslipidemia, and other metabolic syndrome markers. However, the action of angiotensin-converting enzyme 2 (ACE2) and gut health in systemic homeostasis vary, and their interaction is not completely understood. Methods We adopted a combinatory approach of metabolomics and fecal 16S rRNA analysis to investigate gut microbiota and metabolite in two different mouse models, ACE2 knockout (ACE2 KO) mice and the ACE2-overexpressing obese mice. Results 16S rRNA gene sequencing revealed that ACE2 influences microbial community composition and function, and ACE2 KO mice had increased Deferribacteres, Alcaligenaceae, Parasutterella, Catenibacterium, and Anaerotruncus, with decreased short-chain fatty acid (SCFA)-producing bacteria (Marvinbryantia and Alistipes). In contrast, ACE2-overexpressed mice exhibited increased anti-inflammatory probiotic (Oscillospiraceae, Marinifilaceae, and Bifidobacteriaceae) and SCFA-producing microbes (Rikenellaceae, Muribaculaceae, Ruminococcaceae, Odoribacter, and Alistipes) and decreased Firmicutes/Bacteroidetes, Lactobacillaceae, Erysipelotrichaceae, and Lachnospiraceae. Metabolome analysis indicated differential metabolites in ACE2 KO and ACE2-overexpression mice, especially the glucolipid metabolism-related compounds. Furthermore, correlation analysis between gut microbiota and metabolites showed a dynamic mutual influence affecting host health. Conclusion Our study confirms for the first time a significant association between ACE2 status and gut microbiome and metabolome profiles, providing a novel mechanism for the positive effect of ACE2 on energy homeostasis.